Plany oblężenia Kamieńca Podolskiego w 1672 roku - Opyrchał, Leszek; Recław-Mastronardi, Justyna (Przegląd Wschodnioeuropejski, 2023)
The article discusses two undated, handwritten plans for the Kamieniec Podolski fortress in 1672. The first plan (Paris) has descriptions in French and Turkish and shows the location of individual Ottoman units during the siege of Kamieniec Podolski in 1672. The second plan (Bologna) is very similar to the Paris plan. It was provided with a legend made later in Italian, but its contents do not indicate the date of its creation. A comparison of the view of the fortifications (the Black Tower and the Turkish Bridge) with other plans shows that the Bologna plan is an unfinished copy of the Paris plan and was made between the years 1672-1685, most likely after the fortress was conquered by the Ottoman army in 1672. This is evidenced by the minarets located in the city.